Assessing the sensitivity and responsiveness of Early Childhood Oral Health Impact Scale to routine dental treatments on life quality of preschool children in Isfahan in 2011 - Morteza Saleki; Seyed Ebrahim Jabbarifar; Shima Soheilipour; Fatemeh Hajjizadeh (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Early Childhood Oral Health Impact Scale (ECOHIS) is a measure which can assess oral health-related quality of life (OHRQoL). The scale questionnaire has already been translated into Farsi and its validity and reliability have been tested. This study aimed to investigate the sensitivity and responsiveness of the Farsi version of the Early Childhood Oral Health Impact Scale (F-ECOHIS) to routine dental treatments in preschool children.Materials and methods: In the descriptive-analytical study a simple sampling procedure was carried out to select 143 parents of 2-5 year-old children, attending a dental clinic, to complete F-ECOHIS prior to and 1 month after their child's routine dental treatment. In addition, the parents rated the changes they expect in their child's oral health condition, compared to pre-treatment period, based on a global transition scale. Sensitivity of the measure was assessed by determining changes in ECOHIS scores; responsiveness was assessed by investigating whether the observed clinical changes were consistent with the changes expected, in terms of the changes observed in life quality and effect size. Data were analyzed by Wilcoxon's signed-rank test.Results: Following routine dental treatment, there were significant changes in F-ECOHIS scores before and after treatment (p value = 0.001). Means and standard deviations of questionnaire scores before and after treatment were (22.3 ± 9.4) and (13.2 ± 6.3), respectively. Life quality gradient was consistent with changes of ECOHIS scores in relation to the quality of life expected and assessed by parents, supporting the responsiveness of the measure.Conclusion: The F-ECOHIS is sensitive and responsive to routine dental treatments in preschool children.   Key words: Dental, Quality of life, Sensitivity.